Role of hydraulic residence time in shaping phytoplankton community assembly in the upper yellow river cascade reservoirs - Luo, Qiyong; Zhu, Linyu; Li, Daikui; Zu, Zhigang; Chen, Kebin; Wang, Jia; Yi, Yujun (Frontiers in Environmental Science, 2025)
Introduction: Cascade hydropower development significantly alters the structure and function of river ecosystems. Phytoplankton, as primary producers, are highly sensitive to environmental changes, and their diversity and community structure reflect the state of the water environment. While there is extensive research on how changes in river environments affect phytoplankton community structure, studies on the spatial distribution patterns and community assembly mechanisms of phytoplankton in relation to hydraulic residence time (HRT)—a key characteristic of reservoirs—are limited.Methods: Linear regression analysis was used to examine the relationship between phytoplankton communities and HRT. Additionally, the Neutral Community Model (NCM) combined with the Modified Stochasticity Ratio (MST) was employed to reveal the types of phytoplankton community assembly in these cascade reservoirs. Finally, Mantel tests and stepwise regression analysis assessed the specific impacts of environmental factors on phytoplankton communities.Results: In the ecosystem of the Yellow River cascade reservoirs, HRT is positively correlated with phytoplankton abundance and diversity across different seasons. In annual regulation hydropower stations (LJX and LYX), phytoplankton species richness, abundance, and diversity indices are higher compared to those in runoff hydropower stations.Discussion: The phytoplankton community assembly is primarily driven by deterministic processes, with annual regulation hydropower station being more influenced by these processes than runoff hydropower station. HRT, water temperature (WT), and total nitrogen (TN) are the most significant environmental factors affecting the structural differences of phytoplankton in cascade reservoirs. There is a significant positive correlation between phytoplankton and water temperature, especially in short HRT runoff hydropower station where phytoplankton abundance is more significantly impacted by water temperature.